Adult Newcomers and Immigrants in North America: Promising Pathways for Transformative Learning - Karen Magro (Adult Education Research Conference, 2012)
More people are on the move today and migration is recognized as one of the defining global issues of the 21st century. Available information suggests that there are about 194 million people living outside their place of birth. There is growing recognition that migration is an essential and inevitable component for the economic and social life of Canada. Immigration today has become more complex as individuals attempt to reestablish their lives and livelihoods in cultural contexts very incongruous to ones they left. Learning and cultural integration can be a lifelong process that involves struggle, loss, negotiation, and transformation. Navigating a new culture requires the ability to learn new emotional, social, cultural, academic and work related skills in a short period of time.